2023
DOI: 10.1002/jbm.b.35232
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐deposited diatom‐biosilica enhanced osteogenic potential in periodontal ligament stem cells and rat cranium

Abstract: This study aimed to establish that copper-deposited Diatom-biosilica have the potential and possibility for clinical applications in repairing bone defects in a state of inflammation, such as periodontitis. Treatment of alveolar bone defects caused by periodontitis is a major challenge for clinicians. To achieve better repair results, the material should not only be bone conductive but also have the ability to stimulate osteogenesis and angiogenesis at the lesion site. Copper (II) and silicon (IV) ions could r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…The osteogenic, angiogenic, and anti-inflammatory properties of Cu were also highlighted in other recent studies, such as using Cu-doped mineralized diatom (Cu-DBs) [176] and borosilicate glass bone cement [177]. Notably, Li S. and colleagues found that Cu can accelerate bone healing thanks to its anti-inflammatory, angiogenic, and osteogenic properties [177].…”
Section: Effects Of Copper In Bone and Cartilage Tissuesmentioning
confidence: 77%
“…The osteogenic, angiogenic, and anti-inflammatory properties of Cu were also highlighted in other recent studies, such as using Cu-doped mineralized diatom (Cu-DBs) [176] and borosilicate glass bone cement [177]. Notably, Li S. and colleagues found that Cu can accelerate bone healing thanks to its anti-inflammatory, angiogenic, and osteogenic properties [177].…”
Section: Effects Of Copper In Bone and Cartilage Tissuesmentioning
confidence: 77%
“…These results indicated that the presence of diatom BS enhanced the mineralization ability of BCB scaffold. Many previous studies conducted alizarin red S staining to detect the osteogenic differentiation and reported that the addition of diatom BS to scaffolds increased the intensity of calcium nodules and thus the degree of mineralization 6 , 51 53 .
Figure 5 Alizarin red S staining of ( a ) MSCs cultured in ODM on the surface of well-plate (Scale bar: 20 µm), ( b ) blank (cell-free) BCB scaffold (Scale bar: 200 µm), ( c ) MSCs cultured in ODM on CB scaffold (Scale bar: 200 µm), ( d ) MSCs cultured in ODM on BCB scaffold (Scale bar: 500 µm) ( e ) Quantitative analysis of alizarin red S staining of CB and BCB scaffolds in GM and ODM after 28 days of incubation (ns; p > 0.05, *p < 0.05).
…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the presence of diatom BS enhanced the mineralization ability of BCB scaffold. Many previous studies conducted alizarin red S staining to detect the osteogenic differentiation and reported that the addition of diatom BS to scaffolds increased the intensity of calcium nodules and thus the degree of mineralization 6,[51][52][53] .…”
Section: Osteogenic Differentiation In Vitromentioning
confidence: 99%